Rapid Improvement in Inflammatory Markers Before and After Vamana Karma in Peenasa (Sinusitis) - Rajendra, Patel Muktiben; Matekar, Manjula; Shrivastava, Gaurav; Gupta, Richa Girishchandra (Journal of Neonatal Surgery, 2025)
Background: Peenasa, described in Ayurveda as a Vata-Kaphaja disorder correlating to sinusitis, is a common and chronic condition characterized by inflammation of the paranasal sinuses. Conventional treatments (antibiotics, decongestants, antihistamines, etc.) often provide only temporary symptomatic relief while the underlying pathology persists. Ayurvedic classics recommend Vamana karma (therapeutic emesis) for Peenasa, and prior studies have reported significant improvement in sinusitis symptoms with Vamana therapy. Objective: This pilot study aimed to evaluate the rapid effects of Vamana karma on objective inflammatory markers – total leukocyte (WBC) count, eosinophil count and erythrocyte sedimentation rate (ESR) – in patients with chronic sinusitis. Methods: Five patients (ages 27–35; 2 males, 3 females) diagnosed with Peenasa (sinusitis) underwent classical Vamana karma. Baseline and 7-day post-treatment values of WBC, eosinophils, and ESR were measured. Data were analyzed using paired t-tests to assess statistically significant changes. Results: All patients exhibited a notable reduction in inflammatory markers within one week. The mean WBC count decreased from 9380 to 7460 per µL (∼20% drop, p<0.005), mean eosinophil count from 590 to 488 per µL (∼17% drop, p<0.001), and mean ESR from 17.6 to 13.6 mm/hr (∼23% drop, p<0.005). These changes were statistically significant. Each individual showed a downward trend in these markers after Vamana. Conclusion: Vamana therapy was associated with rapid and significant improvement in objective markers of inflammation in sinusitis patients. This suggests that Vamana not only provides symptomatic relief as noted in Ayurveda, but also measurably reduces underlying inflammatory and allergic processes in the short term. While limited by small sample size, this preliminary evidence supports Vamana karma as a potential integrative approach for managing chronic sinusitis. Larger controlled studies are recommended to confirm these findings and assess long-term outcomes.